Biospecific interaction (affinity) CEC and affinity nano-LC - Okanda, Fred M.; El Rassi, Ziad (Electrophoresis, 2007)
This review article is aimed at assessing the recent progress made in affinity nano‐LC and affinity CEC performed in capillaries and microchips. A variety of biospecific interactions is covered including lectin affinity, immunoaffinity, immobilized metal affinity, sugar‐based affinity, protein A affinity, protein G affinity, aptamer affinity, enzyme affinity, and other miscellanea. ACE involving affinity interaction in free solution is not covered in this review article. Also, affinity‐based separations involving chiral recognition are not the subject of this review article because they are the topic of a more specialized review article on chiral separations in this special issue. A total of 31 papers published in the period 1998–2006 have been discussed in this review article.